2017
DOI: 10.1021/acs.jpcb.7b04835
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation of Divinyl Chlorophyll a/b-Containing Cyanobacterium to Different Light Conditions: Three Strains of Prochlorococcus marinus

Abstract: The light-harvesting mechanisms in the three strains of Prochlorococcus marinus, CCMP1986, CCMP1375, and CCMP2773, grown under blue and red light-emitting diodes (LEDs) at two intensity levels were investigated. The blue LED was divinyl chlorophyll b (DV-Chl b) selective and the red LED was DV-Chl a selective. Under the red LED, the relative amount of DV-Chl b in CCMP1375 and CCMP2773 decreased and the relative amount of zeaxanthin increased in CCMP1375. Furthermore, the pigment composition of cells of CCMP137… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 29 publications
(80 reference statements)
2
11
0
Order By: Relevance
“…Values shown are mean values for biological replicates ± s.d, n ≥ 2. Letters represent significant groupings from one-way ANOVA and HSD post hoc tests (p < 0.05) ◂ acclimation to a perceived lower light environment despite the constant PAR between the different light sources. Similar acclimation responses were found by Hamada et al (2017) where pigment ratios of chlorophylls and carotenoids were found to change under different light spectra at the same light intensity in P. marinus. Lower α and higher E K were derived from P v I curve parameters from Bright White LED cultures (lowest PUR), compared to the Kyocera LED cultures (Fig.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Values shown are mean values for biological replicates ± s.d, n ≥ 2. Letters represent significant groupings from one-way ANOVA and HSD post hoc tests (p < 0.05) ◂ acclimation to a perceived lower light environment despite the constant PAR between the different light sources. Similar acclimation responses were found by Hamada et al (2017) where pigment ratios of chlorophylls and carotenoids were found to change under different light spectra at the same light intensity in P. marinus. Lower α and higher E K were derived from P v I curve parameters from Bright White LED cultures (lowest PUR), compared to the Kyocera LED cultures (Fig.…”
Section: Discussionsupporting
confidence: 83%
“…This could potentially lead to obscuring of cellular processes which are regulated both by sensing light quality and quantity. In addition, some marine P. marinus and Synechococcus strains have been shown to chromatically adapt in order to best match the emission spectra of the light they are exposed to throughout the water column (Palenik 2001;Croce and van Amerongen 2014;Hamada et al 2017;Grébert et al 2018). The ability to chromatically adapt their pigment composition provides a distinct competitive advantage.…”
Section: Discussionmentioning
confidence: 99%
“…1d). The TRF spectra were recorded at 77 K by a time-correlated single-photon counting system with a wavelength interval of 1 nm/channel and a time interval of 2.44 ps/channel 27 . A picosecond pulse diode laser (PiL044X; Advanced Laser Diode Systems, Germany) operated at 445 nm with a repetition rate of 3 MHz was used as the excitation source.…”
Section: Methodsmentioning
confidence: 99%
“…TRF spectra were recorded by a time-correlated single-photon counting system with a wavelength interval of 1 nm and a time interval of 2.44 ps 65 . A picosecond pulse diode laser (PiL044X; Advanced Laser Diode Systems) was used as an excitation source, and it was operated at 445 nm with a repetition rate of 3 MHz.…”
Section: Methodsmentioning
confidence: 99%